1993
DOI: 10.3109/02813439308994900
|View full text |Cite
|
Sign up to set email alerts
|

Frequent attenders in general practice: A study from slovenia

Abstract: To compare frequent with infrequent attenders at GPs' surgeries in a rural area in Slovenia with respect to morbidity, type of contact with the GP, referral pattern and the prescriptions given, a random sample of 623 records from a population-based register was analysed retrospectively. The frequent attenders had a higher proportion of contacts for malignant disease, mental disorder, and gastrointestinal disease. They also had a greater probability for a "superficial contact", were more likely to be referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 2 publications
3
25
0
4
Order By: Relevance
“…Few studies report on the association between FA in primary care and other areas of care [12,17,23]. Our findings indicate as elsewhere that FA behavior is not restricted to family practice as this behavior extends into secondary care and contact with both medical and paramedical services, suggesting unmet need at both the primary and secondary care level.…”
Section: Association Between Fa In Family Practice and Use Of Other Hsupporting
confidence: 75%
See 1 more Smart Citation
“…Few studies report on the association between FA in primary care and other areas of care [12,17,23]. Our findings indicate as elsewhere that FA behavior is not restricted to family practice as this behavior extends into secondary care and contact with both medical and paramedical services, suggesting unmet need at both the primary and secondary care level.…”
Section: Association Between Fa In Family Practice and Use Of Other Hsupporting
confidence: 75%
“…They are clinically heterogeneous exhibiting higher rates of non disease-specific physical and chronic illness [7,[11][12][13]. Higher rates of FA are found in association with mental illness [11,[14][15][16][17][18][19], the likelihood of FA increasing with anxiety disorder by a factor of 1.14 in a multi-adjusted model [19]. FAs also have higher rates of depressive symptoms [15,16,20,21], as well as somatoform symptoms or disorders [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics were significantly more prescribed among most FA groups. The finding that FAs are more likely to receive an antibiotic prescription has been noted previously (2). The fact that the injury diagnoses were increased among FAs in several age groups is interesting.…”
Section: Discussionsupporting
confidence: 57%
“…FAs include those with complicated somatic diseases, but there are also many who seek health care as a result of worry, anxiety, depression, distress and psychosocial problems (1,8,11 Á/14). Previous studies have analysed FAs all as one group (1,5,7 Á/9,15,16) and compared them with a control group of either the remaining attenders at primary health care (2,3,5,8,9,16,17) or with a group of infrequent attenders (1,17). No study has looked at the specific characteristics of FAs within different age bands and sexes and compared them with the rest of the population.…”
mentioning
confidence: 99%
“…This is concordant with previous studies presenting data on the distribution per patient (3,4), and the trend has been indicated in other studies (5, 6, 9, 10, 13, 14, 15). The findings correspond to another well-reported finding, that a few percent of all patients/the population who are frequent attendees, constitute one-quarter of all general practitioner (GP)-visits as well as prescriptions (16,17,18,19,20,21). "Frequent attendees" may have renewals of a prescription long before the expiry of the previous ones, resulting in two or more simultaneous prescriptions for the same treatment.…”
Section: Discussionmentioning
confidence: 56%